Willingness to Adopt Sistem Integrasi Sapi Kelapa Sawit di Kabupaten Wajo - Qinayah, Mirnatul; Sirajuddin, Sitti Nurani; Mutmainnah; Sri Wira Utami; April; Muh. Faisal Rahmat (Universitas Islam Negeri Alauddin Makassar, 2025)
The cattle-oil palm integration system (SISKA) is an alternative livestock business development that utilizes the synergy between oil palm plantations and beef cattle. However, the implementation of this system at the farmer level is still limited. This study aims to analyze farmers' willingness to adopt the cattle-oil palm integration system and the factors that influence it in Keera District, Wajo Regency, South Sulawesi. The study was conducted in May–July 2025 using a survey method on 80 farmers selected purposively based on the Events per Variable (EPV) guidelines. Data analysis used binary logistic regression with independent variables including farmer characteristics, access to information, perceived benefits, group membership, extension intensity, and capital support. The results showed that perceived benefits and capital support significantly influenced farmers' willingness to adopt SISKA, while the variables of age, land area, farming experience, access to information, group membership, and extension intensity did not. Scientifically, these findings confirm that the adoption of innovations among smallholder plantation farmers is more influenced by perceived economic benefits and access to resources than by sociodemographic factors or formal institutions. Policy implications indicate the need for a SISKA development strategy that focuses on demonstrating tangible benefits and providing accessible financing schemes to reduce initial investment barriers for smallholder farmers, as well as developing extension strategies that are more tailored to the conditions of farmers in the study area.